4y-3-6y+4=

Simple and best practice solution for 4y-3-6y+4= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4y-3-6y+4= equation:


Simplifying
4y + -3 + -6y + 4 = 0

Reorder the terms:
-3 + 4 + 4y + -6y = 0

Combine like terms: -3 + 4 = 1
1 + 4y + -6y = 0

Combine like terms: 4y + -6y = -2y
1 + -2y = 0

Solving
1 + -2y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + -2y = 0 + -1

Combine like terms: 1 + -1 = 0
0 + -2y = 0 + -1
-2y = 0 + -1

Combine like terms: 0 + -1 = -1
-2y = -1

Divide each side by '-2'.
y = 0.5

Simplifying
y = 0.5

See similar equations:

| X^2/x+100=50 | | N/3.5=12 | | -3[-4-6y]+7[-y+5]=-8 | | N/8=5.9 | | 3(k+8)-2(3k+8)= | | N/15=14 | | 2/x-9 | | N/3=7.5 | | 5u^2-6u-2= | | N/4=19 | | 6.5x-3+x-1.4= | | N/8=25 | | 5[4+2x]-[8x-12]=68 | | N/2=17 | | 8x+8-4(x+1)=9x+7 | | 102=84+6(h) | | (-3/5)^0 | | -3/5^0 | | -6[x-2]+4[3-6x]=-36 | | 9x+2-3=7 | | -5(4x-5)+5=-20x+30 | | x+6y+4z=12 | | 9x+2-3=-3+9x | | 40x+4-3y= | | g/7=-21 | | 2(x+5)=4x-7(x+3) | | 12x^3-2x^2-30x=0 | | 5(3-2x)=8-6(2-5x) | | 11x+233y= | | 8/x-7 | | 1.2=14.4 | | y=1000+5x |

Equations solver categories